2020
DOI: 10.3390/agronomy10091331
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural and Forest Land-Use Impact on Soil Properties in Zagreb Periurban Area (Croatia)

Abstract: In urban areas, land use usually increases soil degradation. However, there are areas occupied by agriculture and woodlands with an essential role in provisioning food and other services such as water and climate regulation. The objective of this work was to assess the effect of long-term land use and soil management practices on peri-urban soils in Zagreb (Croatia). Samples were collected at depth 0–10 cm within intensively tilled cropland (CROP) and vineyard (VINE), traditional grass-covered orchard (ORCH), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 85 publications
2
10
0
Order By: Relevance
“…Land use changing can change land cover and associated carbon stocks (Deng et al, 2014). The results of present study are in agreement with those of Bogunovic et al (2020), in which the organic matter stocks were higher in the forest soil compared to the plots with intensively tilled cropland, vineyard, and traditional grass-covered orchard. Similarly, losses of organic matter stocks after forest to cropland conversion have mostly been reported in previous studies (Beheshti et al, 2012;Wang et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Land use changing can change land cover and associated carbon stocks (Deng et al, 2014). The results of present study are in agreement with those of Bogunovic et al (2020), in which the organic matter stocks were higher in the forest soil compared to the plots with intensively tilled cropland, vineyard, and traditional grass-covered orchard. Similarly, losses of organic matter stocks after forest to cropland conversion have mostly been reported in previous studies (Beheshti et al, 2012;Wang et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…Compared to forest soil, recorded values of bulk and real density are higher in agricultural land subjected to various types of agricultural use (Bogunovic et al, 2020). In the study of Bini et al (2013), lower densities were observed in soils that were subject to less anthropogenic intervention such as natural forests.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Other research has evaluated peri-urban agricultural multifunctionality and agroecosystem services [37][38][39][40]. Research has noted the diverse functions of urban agriculture [41,42], providing a variety of ES [43] but also producing many negative services [44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…These socio-ecological maps can be used in the study of scenarios of change and, therefore, in the management of the sustainability. The drivers of change (e.g., emigration, aging or land-use changes, including intensification) [10,11] will transform the socio-ecological landscape, modifying not only spatial units but also spatial boundaries, affecting the delivery of ecosystem services.…”
Section: Introductionmentioning
confidence: 99%